Ocular Surface Disease A Case-Based Guide (Springer International Publishing, 2018)
Using a case-based format to help disseminate some of the hard-to-find information on ocular surface disease, this book is written and edited by leaders in this rapidly evolving field. Each chapter is built around three actual patient cases with varying degrees of complexity whereby detailed aspects of the care are described in order to provide practical information and illustrate real world challenges. Ocular Surface Disease covers the most common disorders, ranging from dry eye disease and tear film insufficiency to the more severe cicatricial diseases. The role and application of both medical and surgical treatments are carefully explained. The book is intended for ophthalmologists, both in practice or in training, who are seeking an update on the more advanced clinical practices.